Development in Late Adulthood – Opportunities and Threats - Finogenow, Maria (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
According to the principles of life-span psychology, development is a lifetime process that lasts from birth to death. It is multi-dimensional in nature and encompasses both progressive and regressive change.The paper focuses on developmental changes typical of the last period of life, and investigates limitations and barriers impeding personal development in the elderly. Personality traits that may prevent positive adaptation to the old age are indicated, together with the opportunities for development in late adulthood and the factors conducive to positive ageing.